Credit risk management in Ghanaian Banks: a case study of SG-SSB Limited - Baabereyir, Edmund Bertino (2014)
A thesis submitted to the Institute of Distance Learning, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirements for the award of Commonwealth Executive Masters of Business Administration